Analisa Kompetensi Lulusan Sarjana Komputer Melalui Situs Lowongan Kerja Menggunakan Metode SMART - Rachmawati, Eka Putri; Hidayati, Nurtriana; Zaman, Badroe (LPPM STIKOM Tunas Bangsa, 2024)
Meeting workforce needs goes beyond producing a certain number of graduates; it requires computer science graduates possessing essential competencies sought by companies. The government supports competency development through Regulation Number 59 of 2018, overseeing the Certificate of Accompanying Diploma (SKPI) and Competency Certificates. Students are encouraged to participate in extracurricular activities to enhance job-relevant competencies. This study, utilizing the Simple Multi Attribute Rating Technique (SMART), assesses the competencies in demand for computer science graduates via popular job vacancy websites. Data from JobStreet, LinkedIn, and Karir reveal the most sought-after competencies, considering keyword searches, Final Project concentrations at Semarang University's Information Technology Department, and alignment with Ministry of Manpower projections in the Information and Communication Technology (ICT) sector. Job vacancies congruent with these projections receive scores. The SMART method results show that (Software) Developer is the most prominently sought competency on job vacancy websites.